Perdas auditivas induzidas pelo ruído em militares: um enfoque preventivo - Godoy, Tereza Cristina Messina (1991)
This paper has had the purposes of studying the uprising and gradual development of hearing losses noise—induced (HLNI) on military personnel paying special attention to the compromising degree and the time of development of the losses and discussing some proposals of hearing conservation. 509 male subjects of 28 specialities were examined at the beginning of the course and 20 months later, when the course finished. It was proposed a criterium to classify the hearing losses, reducing the range of normality to hearing levels lower than or equal to 20 dB, aiming the detection of the HLNI earliest. The results indicated a significant number of subject presenting changes on hearing by the end of the course. Those changes occurred mainly among subject exposed to noise levels above to 80 dB (A)but among subjects exposed to noise levels below 70 dB (A). was observed s small degree of worsening on hearing. HLNI were made known bilaterally and the 6000 Hz frequency was the most involved one. Other than those subjects exposed to levels higer than 80 db(A), exposed to levels between 70 and 80 dB (A), showed losses too, what points out the necessity of reevaluating of the limits of exposure to the noise prescribed by the legislation, determining thus a level of action from which standards of hearing preservation can be proposed